Pre-clinical In Vitro Models of Vascular Graft Coating in the Prevention of Vascular Graft Infection: A Systematic Review. (January 2022) - Mufty, Hozan; Van Den Eynde, Jef; Meuris, Bart; Metsemakers, Willem-Jan; Van Wijngaerden, Eric; Vandendriessche, Thomas; Steenackers, Hans P.; Fourneau, Inge
Abstract : Objective: Vascular graft infection (VGI) is a feared complication. Prevention is of the utmost importance and vascular graft coatings (VGCs) could offer a potential to do this, with in vitro research a first crucial step. The aim of this study was to summarise key features of in vitro models investigating coating strategies to prevent VGI in order to provide guidance for the setup of future translational research. Data sources: A comprehensive search was performed in MEDLINE, Embase, and Web of Science. Methods: A systematic review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines. For each database, a specific search strategy was developed. Quality was assessed with the Toxicological data Reliability Assessment Tool (ToxRTool). In vitro models using a VGC and inoculation of the graft with a pathogen were included. The type of graft, coating, and pathogen were summarised. The outcome assessment in each study was evaluated. Results: In total, 4 667 studies were identified, of which 45 papers met the inclusion criteria. The majority used polyester grafts (68.2%). Thirty-one studies (68.9%) included antibiotics, and nine studies (20%) used a commercial silver graft in their protocol. New antibacterial strategies (e.g., proteolytic enzymes) were investigated. A variety of testing methods was found and focused mainly on bacterial adherence, coating adherence and dilution, biofilm formation, and cytotoxicity. Ninety-three per cent of the studies ( n  = 41) were considered unreliable. Conclusion: Polyester is the preferred type of graft to coat on. The majority of coating studies are based on antibiotics; however, new coating strategies (e.g., antibiofilm coating) are coming. Many in vitro setups are available. In vitro studies have great potential, they can limit the use, but cannot replace in vivo studies completely. This paper can be used as a guidance document for future in vitro research.